2021
DOI: 10.1007/s10648-021-09597-7
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism in Academically Gifted Students: A Systematic Review

Abstract: Perfectionism has long been recognised as a psychological factor that can enhance or interfere with the healthy adjustment of young students who are academically gifted. However, it is apparent from existing research that a wide range of methods have been adopted to study perfectionism in this population. To identify what is currently known about perfectionism among these students and what future work needs to be undertaken, a systematic review of existing research is required. The aim of our study was to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 76 publications
0
6
0
1
Order By: Relevance
“…We assessed the methodological quality of all included primary studies. Based on a previously used quality assessment tool (Grugan et al, 2021) and general recommendations for assessing primary study quality (Petticrew & Roberts, 2008), we developed an instrument for quality assessment tailored specifically for the present review. We included the following quality dimensions: (i) measurement of multidimensional perfectionism, (ii) measurement of sleep disturbance, (iii) research design, (iv) sample size, (v) sample design, and (vi) peer‐review status.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed the methodological quality of all included primary studies. Based on a previously used quality assessment tool (Grugan et al, 2021) and general recommendations for assessing primary study quality (Petticrew & Roberts, 2008), we developed an instrument for quality assessment tailored specifically for the present review. We included the following quality dimensions: (i) measurement of multidimensional perfectionism, (ii) measurement of sleep disturbance, (iii) research design, (iv) sample size, (v) sample design, and (vi) peer‐review status.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the two‐dimensional perfectionism model (e.g., Stoeber & Otto, 2006) differentiates two broader dimensions, namely perfectionistic concerns (also labelled evaluative concerns perfectionism) and perfectionistic strivings (also labelled personal standards perfectionism). This perfectionism model is commonly accepted and frequently used for research syntheses (e.g., Burcaş & Creţu, 2020; Dahlenburg et al, 2019; Grugan et al, 2021; Ocampo et al, 2020; Osenk et al, 2020; Robinson & Wade, 2021; Smith et al, 2019, 2021; Stricker et al, 2019; Vacca et al, 2021). Previous work showed that, compared to perfectionistic strivings, perfectionistic concerns are more consistently and strongly related to mental health difficulties (e.g., Burcaş & Creţu, 2020; Vacca et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Siegle et al (2020) examined this e ect in their study of perspectives of overachieving GATS, deducing that when GATS have confidence in their skills, they have high levels of self-e cacy. The mixture of a fear of failure and a pattern of high academic performance plagues GATS with perfectionistic concerns (Grugan et al, 2021). The pressure of maintaining an academic standing and keeping up with the high-achieving students in my class made me obsess over having a flawless academic record.…”
Section: Impairment Of Students' Academic Self-conceptmentioning
confidence: 99%
“…Кризисы профессионального обучения (например, кризис третьего года обучения) отрицательно отражаются на отношении студентов к себе [39]. Самооценка является не только основным фактором адаптации к обучению в вузе [40], но и условием формирования специфичных стратегий обучения первокурсников (ориентация на процесс или результат обучения, стремление к получению диплома или получению высоких оценок и др.) [41].…”
Section: обзор литературыunclassified